El futuro de los humanismos en la administración (2019)
Based on the catastrophic secondary effects of business management, the author justifies the need for a change in administrative and organizational thought in order to try to conciliate the goals of the enterprises with humanistic and environmental imperatives. The article shows the attempts of the last three decades to find alternatives for an epistemological reformulation of management, without significant results. On the contrary, the outlook seems more and more gloomy. The proposal of the author is then to look for a possible solution on a higher level, the ontological one, for which he refers to Gadamer’s concept of Bildung to carry out a proposal for an integral education of managers.